RURAL CREDIT MARKET AND INSTITUTIONAL TRANSFORMATION: EVIDENCE FROM JEMBER REGENCY, EAST JAVA, INDONESIA - Adhitya Wardhono (UPT Penerbitan Universitas Jember, 2012)
The Indonesian farmers still face some problems related to the limitation of resources such as a lack of capital to improve their production. Hence, rural credit markets are still needed as stimulants for agricultural production. Agricultural performances are characterized by a time lag between planting and harvesting, and farmers are typically faced with very little cash revenue during this period. All at once, expenditures for materials, purchased inputs, and consumption must be made in cash. The accessibility of credit allows both greater consumption and volumes of purchased inputs used and, therefore, increases the welfare of the farmers. This paper is intended to investigate the pattern of institutional transformation of rural credit access which existed in Klompangan Village and Jatian Village, Jember This paper also explores pattern of institutional transformation by viewing economic actors of village as subjects. The method used in this paper was in depth-interview and focus group discussion (FGD) in purpose of obtaining information about the process of occurrence of institutional transformation on each study field. The analysis in this paper applied qualitative approach so that it could portray problems of institutional transformation deeply and holistically. The transformation of institutional for credit access existed in both of villages which studied, i.e Klompangan Village and Jatian Village. The role of informal credit institution are minimized rather than the past. Semi-formal and formal credit institutions take dominating part of the credit access on the villages. The transformation of the role of credit institution made consequences for the changing of rule of the game on the credit transaction as well as economic transaction on the villages. The dominating personal guarantee and flexible contract was decreased. Nowadays, the rural credit institutions tend to huge impersonal as well as applying formal contract system.